1995
DOI: 10.1002/hep.1840220436
|View full text |Cite
|
Sign up to set email alerts
|

The effect of partial hepatectomy on tumor growth in rats:In vivo andin vitro studies

Abstract: Residual tumor in the remnant liver after partial hepatectomy (PH) for colorectal liver metastases is a serious clinical problem. This fact is reflected by the high number of recurrences after potentially curative liver resections. Liver regeneration, it appears, might influence the growth of remaining micrometastases in the liver. Using rats, we demonstrated enhancement of growth of a syngeneic colon carcinoma (CC 531) in the remnant liver after Two PH. Fourteen days after PH, tumor weights in the liver were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 66 publications
0
19
1
Order By: Relevance
“…In experiments using rats, partial hepatectomy led to a more significant increase in the engraftment and growth of HCC in the residual liver than sham surgery. (31)(32)(33) However, in studies by Picardo et al and de Jong et al, no difference of engraftment and growth of HCC was found in extrahepatic sites based on whether partial hepatectomy was performed or not. (31,32) In contrast, Asaga et al reported growth enhancement in tumor cells following in vitro administration of serum obtained from rats that had been subjected to partial hepatectomy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In experiments using rats, partial hepatectomy led to a more significant increase in the engraftment and growth of HCC in the residual liver than sham surgery. (31)(32)(33) However, in studies by Picardo et al and de Jong et al, no difference of engraftment and growth of HCC was found in extrahepatic sites based on whether partial hepatectomy was performed or not. (31,32) In contrast, Asaga et al reported growth enhancement in tumor cells following in vitro administration of serum obtained from rats that had been subjected to partial hepatectomy.…”
Section: Discussionmentioning
confidence: 93%
“…(31)(32)(33) However, in studies by Picardo et al and de Jong et al, no difference of engraftment and growth of HCC was found in extrahepatic sites based on whether partial hepatectomy was performed or not. (31,32) In contrast, Asaga et al reported growth enhancement in tumor cells following in vitro administration of serum obtained from rats that had been subjected to partial hepatectomy. (33) In this study, extrahepatic recurrence as well as intrahepatic recurrence was found to increase in patients with HCC beyond the Milan criteria who received SFSG.…”
Section: Discussionmentioning
confidence: 93%
“…Increased tumor growth in the remnant liver after partial liver resection in rats is a phenomenon that has been described by several groups. [24][25][26][27] Thus, we felt it was relevant to study the expression of growth factors and their receptors on primary colorectal carcinomas and their liver metastases in relation to clinicopathological variables and survival. In the present study, patients were selected on the basis of the presence of liver metastases of colorectal carcinomas, in which preoperative investigations did not reveal signs of extrahepatic metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that removal of the primary tumour can be associated with an enhanced tumour growth of residual micro-metastases (1). Experimental animal data show that metastatic growth after liver resection is significantly accelerated in the course of hepatic regeneration (2)(3)(4)(5). However, the exact mechanism of this enhanced tumour growth remains unclear.…”
Section: Introductionmentioning
confidence: 99%